Interpreting the effects of natural organic matter on antimicrobial activity of Ag2S nanoparticles with soft particle theory. (15th November 2018) - Liu, Yulei; Yang, Tao; Wang, Lu; Huang, Zhuangsong; Li, Juan; Cheng, Haijun; Jiang, Jin; Pang, Suyan; Qi, Jingyao; Ma, Jun
Abstract: Natural organic matter (NOM) ubiquitously exists in natural waters and would adsorb onto the particle surface. Previous studies showed that NOM would alleviate the toxicity of nanomaterials, while the mechanism is seldom quantitatively interpreted. Herein, the effects of humic substances [Suwannee River fulvic acid (SRFA) and Suwannee River humic acid (SRHA)] and biomacromolecules [alginate and bovine serum albumin (BSA)] on the aggregation and antimicrobial effects of silver sulfide nanoparticles (Ag2 S-NPs) were investigated. The aggregation kinetics of Ag2 S-NPs in electrolyte solutions were in agreement with the results based on Derjaguin-Landau-Verwey-Overbeek (DLVO) theory. The dynamic light scattering (DLS) results showed that the SRFA, SRHA, alginate and BSA molecules coated on the Ag2 S-NPs surfaces. The NOM coating layer prevented salt-induced coagulation of Ag2 S-NPs, and the effects of BSA and SRHA on Ag2 S-NPs stabilizing were more obvious than that of SRFA and alginate. Flow cytometry analysis results suggested that BSA and SRHA were more effective on alleviating the Ag2 S-NPs induced cell ( Escherichia coli ) membrane damage than SRFA and alginate. After interpreting the electrophoretic mobility (EPM) data of the NOM coated Ag2 S-NPs by Ohshima's soft particle theory, it was found that the thickness of the NOM coating layers followed the orders of BSA > SRHA > alginate > SRFA. The E.coli cell membrane damage level was negatively correlated with the thickness and softness of the coating layer. NOM coating may physically alleviate the contact between NPs and E. coli cells and thus attenuate the extent of cell membrane damage caused by the NP-cell interaction. This work provides a new perspective for quantitatively interpreting the influence of NOM on the environmental behaviors and risks of nanomaterials. Graphical abstract: Image 1 Highlights: NOM enhanced the stability and decreased the biotoxicity of Ag2 S-NPs. The relation between NOM coating and toxicity of Ag2 S-NPs is quantitatively analyzed. Thickness and softness of the coating layer are negatively correlated with toxicity of Ag2 S-NPs.